Positive association between social capital and the quality of health care service: A cross-sectional study. (January 2023) - Pedersen, Louise Møller; Jakobsen, Andreas Lindegaard; Buttenschøn, Henriette Nørmølle; Haagerup, Annette
Abstract: Background: Social capital is an acknowledged theoretical concept in work environment research focusing on collective resources that arise from social networks between employees in the workplace. Social capital is divided into bonding (in the work unit), bridging (between work units), and linking social capital (between the work units and management). However, only a few studies have investigated the relationship between social capital and the quality of health care, which is the key outcome of hospital services. Objective: We investigated the associations between bonding, bridging and two types of linking social capital with the self-reported quality of health care services among Danish hospital employees. Next, we directly compared how social capital, workload and work pace each affected the quality of health care. Design: A cross-sectional study at Regional Hospital West Jutland, Denmark. Data: Questionnaire data were collected from 1589 Danish hospital employees. We used validated scales for social capital, workload, and work pace and self-developed scales for clinical quality, quality of patient involvement, and overall professional quality. Methods: Binary logistic regression analyses were conducted. Results: The analyses showed significant, positive associations of bonding and bridging social capital with all types of quality and negative associations between workload and all types of quality. The work pace was negatively associated with clinical quality. When covariates were included in the model, the associations remained statistically significant and showed no decrease in odds ratios. The marginal effects showed that when bonding and bridging social capital were increased by a single scale point, the predicted probability for a high clinical quality increased by an average of 0.5 percentage points. This increase corresponds to a change in the predicted probability of self-reported high clinical quality from 10% for the lowest reported bridging social capital to 54% for the highest reported bridging social capital. For workload and work pace, the effects were − 0.2 and − 0.3 percentage points, respectively. Discussion & conclusions: This study adds to the literature on positive work environment factors by focusing on social capital and the importance of well-functioning relationships within and especially between hospital units for high-quality health care. Hence, bridging and bonding social capital should be included in theoretical frameworks, as well as in hospital strategies and work environment guidelines to potentially improve the quality of health care services. However, further studies are needed to develop and test the effects of specific social capital interventions on the quality of health care services.